help

Hello, ibanez1608!

\(\displaystyle \text{Solve: }\:\begin{array}{ccccc}(x+1)^2 + (y-1)^2 &=& 5 & [1] \\ (x-1)^2 + (y-2)^2 &=& 10 & [2]\end{array}\)

\(\displaystyle \begin{array}{cccccccc}\text{Simplify [1]:} & x^2+2x+1 + y^2-2y+1 \;=\; 5 & \Rightarrow & x^2 + 2x + y^2 - 2y \;=\; 3 & [3] \\ \text{Simplify [2]:} & x^2 - 2x + 1 + y^2 - 4y + 4 \;=\; 10 & \Rightarrow & x^2-2x+y^2-4y \;=\; 5 & [4] \end{array}\)

\(\displaystyle \text{Subtract [3] - [4]: }\:4x + 2y \:=\:-2 \quad\Rightarrow\quad y \:=\:\text{-}2x-1\;\;[5]\)

\(\displaystyle \text{Substitute into [3]: }\: x^2+2x + (\text{-}2x-1)^2 - 2(\text{-}2x-1) \:=\:3\)

\(\displaystyle \text{Simplify: }\: x^2 + 2x + 4x^2 + 4x + 1 + 4x + 2 \:=\:3\)

. . . . . . . \(\displaystyle 5x^2 + 10x \:=\:0 \quad\Rightarrow\quad 5x(x+2) \:=\:0\)

. . \(\displaystyle \text{Hence: }\: x \;=\;0,\,\text{-}2\)

\(\displaystyle \text{Substitute into [5]: }\:y \;=\;\text{-}1,\:3\)


\(\displaystyle \text{Therefore: }\: (x,\,y) \:=\: (0,\,\text{-}1),\;(\text{-}2,\,3)\)
 
(X+1)2+(y-1)2​=5
(X-1)2+(Y-2)2=10
What is the solution x and y


Assuming that "X" was meant to be "x" and "Y" was meant to be "y", notice that you are given equations of two circles - and the intersection points of those two circles would be your solutions.

Please share your work with us.

You need to read the rules of this forum. Please read the post titled "Read before Posting" at the following URL:

http://www.freemathhelp.com/forum/th...217#post322217

We can help - we only help after you have shown your work - or ask a specific question (e.g. "are these correct?")
 
Hello, ibanez1608!


\(\displaystyle \begin{array}{cccccccc}\text{Simplify [1]:} & x^2+2x+1 + y^2-2y+1 \;=\; 5 & \Rightarrow & x^2 + 2x + y^2 - 2y \;=\; 3 & [3] \\ \text{Simplify [2]:} & x^2 - 2x + 1 + y^2 - 4y + 4 \;=\; 10 & \Rightarrow & x^2-2x+y^2-4y \;=\; 5 & [4] \end{array}\)

\(\displaystyle \text{Subtract [3] - [4]: }\:4x + 2y \:=\:-2 \quad\Rightarrow\quad y \:=\:\text{-}2x-1\;\;[5]\)

\(\displaystyle \text{Substitute into [3]: }\: x^2+2x + (\text{-}2x-1)^2 - 2(\text{-}2x-1) \:=\:3\)

\(\displaystyle \text{Simplify: }\: x^2 + 2x + 4x^2 + 4x + 1 + 4x + 2 \:=\:3\)

. . . . . . . \(\displaystyle 5x^2 + 10x \:=\:0 \quad\Rightarrow\quad 5x(x+2) \:=\:0\)

. . \(\displaystyle \text{Hence: }\: x \;=\;0,\,\text{-}2\)

\(\displaystyle \text{Substitute into [5]: }\:y \;=\;\text{-}1,\:3\)


\(\displaystyle \text{Therefore: }\: (x,\,y) \:=\: (0,\,\text{-}1),\;(\text{-}2,\,3)\)

i love u man
 
Top